A Global Agenda for Household Water Security: Measurement, Monitoring, and Management. (27th May 2021) - Wutich, Amber; Jepson, Wendy E.; Stoler, Justin; Thomson, Patrick; Kooy, Michelle; Brewis, Alexandra; Staddon, Chad; Meehan, Katie
Abstract: Water scholarship has advanced considerably in recent decades. Despite this remarkable progress, water challenges may be growing more quickly than our capacity to solve them. While much progress has been made toward achieving Sustainable Development Goal 6 — water and sanitation for all — new stressors have emerged to threaten this progress. Far from being a problem of the Global South, recent research shows that water insecurity is very much a global phenomenon — and one that has been, until recently, seriously neglected in the Global North. This indicates a strong need for innovative measurement of who experiences water insecurity, new approaches for monitoring the efficacy of water interventions, and more effective management of complex, mobile, and multiple water infrastructures to achieve water security. In this paper, we introduce the Household Water Insecurity approach to addressing these concerns. First, we suggest ways to improve the measurement of water insecurity — pinpointing problems at the household and individual levels — in ways that can inform policymaking with improved precision. Second, we discuss ways that new information and communication technology can improve monitoring and indicate where water infrastructure repairs and investments are most needed. Third, we highlight the need for new approaches to managing complex water infrastructures in more inclusive and democratic ways. Abstract : Research Impact Statement : We present an agenda for Household Water Insecurity research that addresses measurement, monitoring, and management with the goal of enhancing long‐term sustainability and water security for all.